Impacts of seeding rates of different Lolium species on winter overseeding of seashore paspalum in Mediterranean regions: turf quality and suitability for football pitches - Ozkan, Sukru Sezgi; Kir, Behcet (Italian Journal of Agronomy, 2023)
Overseeding is an essential management practice for turf cultivation in winter. Warm-season turfgrasses must be overseeded with cool-season turfgrass in the fall to provide green colour and maintain suitable playing surfaces by preventing wear on the dormant warm-season turfgrass throughout the winter months. The cool-season turfgrass species selected for overseeding affect the success or failure of the process in different ways via interaction with environmental conditions. A 2-year research study was conducted at the experimental areas of the Field Crops Department, Agriculture Faculty, Ege University in Izmir/Turkey during 2016-2018. The objectives of the study were to evaluate the overseeding performances of seashore paspalum cv. Sea Spray with different ryegrass (Lolium) species (diploid perennial ryegrass cv. Sun, tetraploid perennial ryegrass cv. Tetragreen, annual ryegrass cv. Axcella, intermediate ryegrass cv. TransAm), and determine the most suitable seeding rates (50, 75, 100 g m-2) for the Mediterranean climate. In the study, the evaluation of turf performance traits such as colour, visual turf quality, cover, fall and spring transition was conducted in both years. Additionally, some football playing quality traits, including ball rebound, force reduction, and vertical deformation were measured during the research periods. According to the results, tetraploid perennial ryegrass cv. Tetragreen and diploid perennial ryegrass cv. Sun generally performed better than the others. Concerning the overseeding rate, 75 or 100 g m-2 applications are recommended as the most suitable for obtaining good turfgrass quality and football playability.